PENINGKATAN PROFESIONALISME GURU SMP N 1 PALANG MELALUI LESSON STUDY BERBASIS SEKOLAH - Mu'jizatin Fadiana; Suantoko Suantoko; Djoko Apriono; Heny Sulistyaningrum; Arif Unwanullah (LPPM Universitas Bina Bangsa, 2022)
The purpose of this Community Service activity is to increase the professionalism of teachers at the 1st Palang Junior High School, Tuban Regency, East Java Province through the implementation of School-Based Lesson Study. Improving teacher professionalism which is the focus of this activity includes; 1) improving the quality of learning, 2) increasing teacher knowledge about learning materials, 3) increasing teacher knowledge about the learning process, 4) increasing the ability of teachers to observe learning activities, 5) strengthening collegiality relationships between teachers, 6) strengthening the relationship between the implementation of daily learning– days with long-term learning goals, and 7) increasing teacher motivation to always develop. The method used to achieve this goal is to carry out the lesson study stages which consist of the plan-do-see-redesign stage. In the plan stage, the teacher designs learning so that students can learn from learning materials actively. In the do stage, the model teacher carries out learning according to the lesson plan. In the do stage, the principal, lecturers and other teachers act as learning observers with supporting devices in the form of observation sheets. In the see stage, the team conducts discussions in the context of reflection and improvement of learning. The results of the reflection are followed up with a redesign for the next learning design